2015
DOI: 10.1159/000381291
|View full text |Cite
|
Sign up to set email alerts
|

Gout after Living Kidney Donation: Correlations with Demographic Traits and Renal Complications

Abstract: Background: The demographic and clinical correlates of gout after living kidney donation are not well described. Methods: Using a unique database that integrates national registry identifiers of U.S. living kidney donors (1987-2007) with billing claims from a private health insurer (2000-2007), we identified post-donation gout based on medical diagnosis codes or pharmacy fills for gout therapies. The frequencies and demographic correlates of gout after donation were estimated by Cox regression with left- and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
(68 reference statements)
0
25
0
Order By: Relevance
“…Presurgical use of opioid analgesics is increasingly recognized as a predictor of postoperative complications and resource utilization in diverse patient populations, including those undergoing general and orthopedic surgery procedures . Pharmacy fill records offer a nonobtrusive measure of medication use in epidemiologic investigations of populations, including living donors and transplant recipients . We recently linked the national transplant registry with fill records from a large pharmacy claims clearinghouse and found that prescription opioid fills in the year before kidney transplantation were associated with increased risk of complications after the transplant procedure .…”
Section: Introductionmentioning
confidence: 99%
“…Presurgical use of opioid analgesics is increasingly recognized as a predictor of postoperative complications and resource utilization in diverse patient populations, including those undergoing general and orthopedic surgery procedures . Pharmacy fill records offer a nonobtrusive measure of medication use in epidemiologic investigations of populations, including living donors and transplant recipients . We recently linked the national transplant registry with fill records from a large pharmacy claims clearinghouse and found that prescription opioid fills in the year before kidney transplantation were associated with increased risk of complications after the transplant procedure .…”
Section: Introductionmentioning
confidence: 99%
“…A study of 4650 kidney donors from the US including 13.1% African Americans, found that, by 7 years, African Americans were almost twice as likely to develop gout as white donors (4.4% vs 2.4%; adjusted HR, 1.0 1.8 3.2 ). 204 Postdonation gout risk also increased with older age at donation and was nearly 3-times higher in men compared with women. 204 In nondonor populations hyperuricemia is associated with a higher risk of CVD and new-onset CKD.…”
Section: Rationale Hyperuricemia and Goutmentioning
confidence: 98%
“…204 Postdonation gout risk also increased with older age at donation and was nearly 3-times higher in men compared with women. 204 In nondonor populations hyperuricemia is associated with a higher risk of CVD and new-onset CKD. 203,205 However, the prognostic significance of hyperuricemia in living kidney donors is currently uncertain and warrants additional study.…”
Section: Rationale Hyperuricemia and Goutmentioning
confidence: 98%
“…A study of 4650 kidney donors from the United States, including 13.1% black donors, found that, by 7 years, black donors were almost twice as likely to develop gout as white donors (4.4% versus 2.4%; aHR, 1.8; 95% CI, 1.0 to 3.2). 49 Postdonation gout risk also increased with older age at donation and was nearly three times higher in men. Compared with matched donors without gout, donors with gout had more frequent diagnoses of renal conditions including ARF, CKD, and other disorders of the kidney.…”
Section: Gestational Hypertensionmentioning
confidence: 98%